The Controversial Role of PD-1 and Its Ligands in Gynecological Malignancies - Marinelli, Oliviero; Annibali, Daniela; Aguzzi, Cristina; Tuyaerts, Sandra; Amant, Frédéric; Morelli, Maria Beatrice; Santoni, Giorgio; Amantini, Consuelo; Maggi, Federica; Nabissi, Massimo (Frontiers in Oncology, 2019)
The programmed death-1 (PD-1, CD279) receptor with its ligands, programmed death ligand 1 (PD-L1, CD274, B7-H1) and programmed death ligand 2 (PD-L2, CD273, B7-DC), are the key players of one of the immune checkpoint pathways inhibiting T- cell activation. PD-L1 and PD-L2 are expressed in different cancer cells and their microenvironment, including infiltrating immune cells. However, their prognostic value is still debated and their role in the tumour microenvironment has not been fully elucidated yet. Considering the importance that cancer immunotherapy with anti-PD-1 and anti-PD-L1 antibodies gained in different tumour types, in this review article we discuss the role of the PD-1/PD-L1/PD-L2 axis in gynaecological cancers. PD-1 ligands have been detected in ovarian, cervical, vulvar and uterine cancers, and correlation with prognosis seems dependent from their distribution. About PD-L2, very few reports are available so far in gynaecological malignancies, and its role is still not completely understood. One of the most promising cancer immunotherapeutic approaches is based on the use of antibodies against inhibitory immune checkpoint molecules, with clinical trials using anti-PD-1 or anti-PD-L1 antibodies, but not anti-PD-L2, currently ongoing, in particular for ovarian cancer. They have shown good safety profiles in a certain cohort of patients, but response rates remain low and many aspects remain controversial. Regarding PD-L2, it might be useful to better clarify its role in order to improve the efficiency of immunotherapy in female malignancies.